2007
DOI: 10.1080/09595230701373917
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of diversion and aftercare strategies for adult drug‐involved offenders: a summary and methodological review of the outcome literature

Abstract: Diversion strategies aim to redirect drug-involved offenders away from the criminal justice system and into treatment. Despite the interest in diversionary practices, the emergence of an empirical evaluation literature has been slow. A methodological review of published outcome studies was conducted to investigate the current strength of evidence for the efficacy of diversion and aftercare practices for criminal offenders. Twenty outcome studies were identified for review: 19 on diversion and one on aftercare.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 52 publications
4
24
0
1
Order By: Relevance
“…In a recent literature review, three-quarters of the 19 studies reviewed identified a reduction in offending following participation in a diversion program [2]. For example, participants in a USA-based diversion program were significantly less likely to be arrested over a 30 month follow-up period in comparison to a matched sample of non-participants [6].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a recent literature review, three-quarters of the 19 studies reviewed identified a reduction in offending following participation in a diversion program [2]. For example, participants in a USA-based diversion program were significantly less likely to be arrested over a 30 month follow-up period in comparison to a matched sample of non-participants [6].…”
Section: Introductionmentioning
confidence: 98%
“…Although individual programs differ, broadly, the aim of diversion is to provide appropriate treatment and support to drugusing offenders to assist in reducing their drug use and criminal recidivism [2,3]. Diversion programs can operate at various stages of the criminal justice system, including arrest, pre-plea or sentencing.…”
Section: Introductionmentioning
confidence: 99%
“…Often, the substance use treatment that is offered in correctional facilities is educational in nature, lacking in the clinical depth required to attend to the needs of people with well-established drug use (Taxman et al, 2007). This is surprising given that extensive research has shown that in criminal justice populations, various modalities of substance use treatment reduce both substance use and criminal justice system involvement (Chandler et al, 2009), including therapeutic communities (TCs), drug courts (Bahr, Masters, & Taylor, 2012;Harvey, Shakeshaft, Hetherington, Sannibale, & Mattick, 2007;Lurigio, 2000), cognitive behavioral therapy (CBT; Bahr et al, 2012;Barnes, Hyatt, & Sherman, 2016), medication-assisted treatment (Lee et al, 2016;Kinlock, Gordon, Schwartz, Fitzgerald, & O'Grady, 2009;Sharma et al, 2016), outpatient group counseling (Welsh, Zajac, & Bucklen, 2014), and meditation (Bowen et al, 2006;Himelstein, 2011). Despite demonstrated efficacy, Lurigio (2000) cautions that substance use treatment is not a cure-all and that treatment must meet the diverse needs of people in the criminal justice system, while also recognizing the chronic and often enduring nature of substance use problems.…”
Section: Introductionmentioning
confidence: 99%
“…This search strategy identified 119 articles, the titles of which were printed and reviewed. Using categories adapted from a number of previous reviews, 1,15,16 the articles were classified as reviews, measures, descriptive, intervention, dissemination, comment or book review or editorial, and other (extracts of original articles, media articles, not primarily alcohol‐related, presentations, submissions to government agencies and theses). In addition to these previously used categories, a number of the articles in this database were identified as resources, rather than articles.…”
Section: Indigenous‐specific Intervention Studies 2000–07mentioning
confidence: 99%